Plant-induced bacterial gene silencing: a novel control method for bacterial wilt disease - Jang, Seonghan; Kim, Doyeon; Lee, Soohyun; Ryu, Choong-Min (Frontiers in Plant Science, 2024)
Ralstonia pseudosolanacearum, a notorious phytopathogen, is responsible for causing bacterial wilt, leading to significant economic losses globally in many crops within the Solanaceae family. Despite various cultural and chemical control strategies, managing bacterial wilt remains a substantial challenge. This study demonstrates, for the first time, the effective use of plant-induced bacterial gene silencing against R. pseudosolanacearum, facilitated by Tobacco rattle virus-mediated gene silencing, to control bacterial wilt symptoms in Nicotiana benthamiana. The methodology described in this study could be utilized to identify novel phytobacterial virulence factors through both forward and reverse genetic approaches. To validate plant-induced gene silencing, small RNA fractions extracted from plant exudates were employed to silence bacterial gene expression, as indicated by the reduction in the expression of GFP and virulence genes in R. pseudosolanacearum.Furthermore, treatment of human and plant pathogenic Gram-negative and Gram-positive bacteria with plant-generated small RNAs resulted in the silencing of target genes within 48 hours. Taken together, the results suggest that this technology could be applied under field conditions, offering precise, gene-based control of target bacterial pathogens while preserving the indigenous microbiota.